Building the CSI-UNMSM environmental education network - Lovera, Daniel (2003)
This article proposes a historical analysis of the initiatives in Environmental Education of international organizations: United Nations Environment Program (UNEP) and the United Nations Educational, Scientific and Cultural Organization (UNESCO). In this context, the National University of San Marcos (UNMSM) establishes a series of activities, such as: postgraduate programs in Environmental Sciences, courses, workshops and environmental protection campaigns. And through the Higher Research Council (CSI), environmental studies are carried out in the different Research Institutes and Centers, likewise, committees are formed and Inter-institutional Agreements related to the Environment are prepared. To consolidate these initiatives, the UNMSM Environmental Education Network was created in April 2003 in order to participate in the formation of institutional capacities and participate in the Local and Regional Networks organized in an adequate management of national environmental education. and international.